Responses to iron limitation in two colonies of Stylophora pistillata exposed to high temperature: Implications for coral bleaching - J. Malcolm Shick; Katrina Iglic; Mark L. Wells; Charles G. Trick; Jason Doyle; Walter C. Dunlap (Limnology and Oceanography, 2011)
Exposing the coral Stylophora pistillata to seawater depleted in available iron by complexation with the strong chelator desferrioxamine B reduces the photosynthetic efficiency and alters the pigment composition in its symbiotic algae at high temperatures. Similar effects of iron limitation are known for free‐living algae, but this is the first demonstration of low‐iron stress in a dinoflagellate living endosymbiotically. Maintaining corals at elevated temperature (30°C and 31°C) under diminished iron availability leads to reduced maximum quantum yields ( F v : F m ) of photosystem II (PSII), specifically on brightly illuminated surfaces of the coral. This reduction in maximum quantum yield is due in part to increased photoprotection, indicated by an increase in the photoprotective xanthophyll diatoxanthin, which promotes nonphotochemical quenching of excess light energy to restrict oxidative damage under conditions that impair photosynthetic electron transfer. However, photophysiological changes associated with the lowered maximum quantum yield did not prevent photodamage to PSII under the combined effects of elevated temperature and low iron availability, as shown by the decrease in maximum ( F m ) that was not accompanied by significant change in the minimum ( F o ) fluorescence yield. All of the foregoing is consistent with the potential of iron limitation to contribute to the underlying conditions by which thermal stress evokes the physiological response by corals that culminates in the symbiotic dysfunction of natural bleaching.